2011
DOI: 10.1289/ehp.1002412
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Investigation of Chronic Exposure to Microcystin in Relationship to Childhood Liver Damage in the Three Gorges Reservoir Region, China

Abstract: Background: Microcystin-producing Microcystis bloom is a severe water problem in the world. Some reports indicate that chronic exposure to microcystin may result in liver damage in adults, but information on effects in children is limited.Objective: We investigated the relationship between microcystin exposure and liver damage in children.Methods: We measured microcystin concentrations in drinking water and aquatic food (carp and duck) from two lakes and four wells. Participants were 1,322 children 7–15 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(103 citation statements)
references
References 25 publications
2
100
1
Order By: Relevance
“…Several reports have described the accumulation of microcystins in edible parts (mainly muscle) of aquatic products (shellfish, crustaceans, fishes, frogs, turtles, water birds, etc.) [3,4,[40][41][42][43][44]. There is also evidence that MCs may be transmitted to cultivated plants from contaminated irrigation water [140].…”
Section: Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have described the accumulation of microcystins in edible parts (mainly muscle) of aquatic products (shellfish, crustaceans, fishes, frogs, turtles, water birds, etc.) [3,4,[40][41][42][43][44]. There is also evidence that MCs may be transmitted to cultivated plants from contaminated irrigation water [140].…”
Section: Humansmentioning
confidence: 99%
“…Consumption of contaminated aquatic products has also been postulated as a key exposure route to MCs. In two recent studies [3,4], MCs were also identified in human serum after chronical exposure via contaminated drinking water and aquatic products.…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be mentioned that other risk factors such as hepatitis B and exposure to aflatoxins from maize and other cereals were also implicated (Ueno et al, 1996). Chronic exposures to water contaminated with MCs at concentrations 1.1-3.28 µg L -1 have been linked with the increased incidence of colorectal cancer (Zhou et al 2002) or liver damage (Chen et al, 2009;Li et al, 2011) in China. In addition, there are reports on statistically significant associations between cyanobacterial blooms and non-alcoholic liver disease in USA (Zhang et al, 2015) or primary liver cancer in Serbia (Svircev et al, 2009(Svircev et al, , 2013(Svircev et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, MCs have been classified as possible human carcinogen (class 2B) by the International Agency for Research on Cancer (Grosse et al, ). In addition, other epidemiological studies associated exposures to toxic cyanobacterial blooms and MCs with chronic liver damage (Chen et al, 2009;Li et al, 2011;Zhang et al, 2015), and MCs were also implicated in neurotoxicity and neurodegenerative diseases (Feurstein et al, 2009(Feurstein et al, , 2010. MCs are therefore regarded as human health hazard.…”
Section: Introductionmentioning
confidence: 99%
“…83 A recent study of children exposed to microcystin from another lake had very high rates of liver cancer. 84 Chinese officials now formally recognize the existence of "cancer villages, " where unusually high rates of cancer are reported as a result of water, as well as other, pollutants. 85 Investments of hundreds of millions of dollars are now being made in sewage upgrades in the Taihu region, 86 which should help to lessen bloom frequency and/or intensity, but pressures from agricultural discharge are likely to continue.…”
Section: Taihumentioning
confidence: 99%